Innovation in Public Sector Management Control Systems in the Context of New Public Management: A Case of an Australian Public Sector Organization - Anup Chowdhury; Nikhil Chandra Shil (Journal of Entrepreneurship, Management and Innovation)

(untitled)
This study is about the exploration of innovative management control systems in the context of New Public Management (NPM) initiatives. NPM initiatives created the changes to the structure and processes of public sector organizations with the objective of getting them to run better. A government department in the Australian Capital Territory (ACT) has been selected as the field for investigation. This study draws on a single theoretical perspective, Giddens’s structuration theory to understand the management control systems evolved in the researched organization. Qualitative research methodology is applied to obtain a better understanding of the phenomena. Case-based research method is used in developing a complete understanding of the relative role of controls in the management of organizational performance. In this study, it is argued that the researched organization has adopted various management control tools to improve its performance and demonstrate transparency and accountability. Some of the control tools it has adopted are the innovations in the public sector. It appears from the case that these adopted management control tools forced the researched organization towards better performance supporting the rationale of adopting New Public Management practices.